ANÁLISIS FINANCIERO A LA COMPAÑÍA HORMICONSTRUCCIONES CÍA. LTDA. DE LA CIUDAD DE LOJA, PERÍODO 2018 – 2019 - Ordóñez Parra, Diana Isabel (2021)
The present degree work called: FINANCIAL ANALYSIS TO THE COMPANY HORMICONSTRUCCIONES CÍA. LTDA. FROM LOJA CITY, PERIODS 2018 - 2019 was developed with the purpose of evaluating the economic and financial position through the variations found in the vertical and horizontal analysis, knowing the levels of liquidity, debt, activity, productivity and profitability through the application of financial indexes established by the Superintendency of Companies; to finally propose policies, conclusions and recommendations that improve the deficiencies found. The elaboration of the work both in its theoretical and practical part is based on the application of different methods, starting from the scientific method that allowed the classification of concepts based on proven theories; followed are the deductive and inductive method with which the information collected was ordered from the general to the most specific; the mathematical method to perform operations; the statistical method that facilitated the consolidation of the data in tables and graphs that allow a better appreciation of the results and finally the analytical and synthetic method used to define policies, conclusions and recommendations that allow the correct decision making. In order to comply with the first specific objective set out in the work, the vertical and horizontal analysis was carried out, calculating the proportional weight and the variations of each of the groups and items that make up the economic and financial structure, of which the most relevant presented within the assets are non-current assets with a weight of 52.69% in 2018 and 55.03% in 2019, this includes property, plant and equipment that is an essential element to comply with the Company activities due to the fact that civil works constructions require the use of machinery, equipment and specialized vehicles in this field. Among the company's liabilities 5 there are some variations, in the 2018 period the one with the highest participation was current liabilities with 55.74%; On the other hand, for 2019 the one with the highest participation is non- current liabilities with 51.05% due to the increase in obligations with financial institutions. Regarding its economic structure, the costs of sale and production are what make the greatest contribution, being 78.87% in 2018 and 75.16% in 2019, these costs being very high affect the decrease in profits. The financial indicators were then applied to meet the second objective, resulting in a high degree of indebtedness in both years, especially in 2019, exceeding 50%, which shows that the company is exposed to more debt by maintaining more debt. to a greater risk of not fulfilling its obligations; Regarding total productivity, the company obtains profits through the use of production factors, however, this is affected by the high level of indirect costs that arise. Another deficiency found through financial indices is that the company is not very profitable because for every dollar in sales a net profit of approximately 0.01 cent is generated in 2018 and 0.02 cents in 2019. To comply with the last objective set for the research, a financial analysis report is presented that includes a synthesis of the results obtained, accounting and financial policies to take into account, conclusions and recommendations that serve as a guide to the partners to improve performance of the company.